(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The growth of pisciculture is increasing in India due to human population growth and other socio-economic factors. The three fish species such as Catla catla, Labeo rohita and Cirrhinus mrigala were cultured in monitored feed supply in two ponds of Gaya town such as Ram Sagar Pond and Dighi Pond. The Fish Meal and Poultry waste Meal mere used during different rearing years in both ponds respectively. The nutritional value of fish muscle such as crude protein (%), crude lipid (%), carbohydrate (%), phosphorus (%) and moisture content (%) were examined to know the impact of different feeds. Moisture content in muscle of Catla catla remained as 77.51-77.65% after application of Fish Meal and 76.46-77.40% after application of Poultry waste meal. The moisture content in muscle of Cirrhinus mrigala remained higher as compared to Catla catla and Labeo rohita reared under both types of diets. Higher value of protein, lipid, carbohydrate and phosphorus were observed in all three fish species after application of Poultry waste meal as compared to Fish meal. So, Poultry waste meal was observed more suitable than Fish meal for rearing of three major carps in Ponds. The data observed for both ponds showed slight variation. This may be due to their physico-chemical parameters.